POLA MODERASI BERAGAMA DALAM RELASI HINDU–KATOLIK DI BANJAR TUKA DESA DALUNG KABUPATEN BADUNG - Watuoto, Sebastian Begobli; Duija, I Nengah; Sena, I Gusti Made Widya (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
Relations between religious communities have given rise to patterns of religious moderation which have become part of the daily lives of people in various parts of the country. Living in harmony, peace and mutual respect between friends and neighbors, between villages and regions as well as between ethnic groups with different religious beliefs has become a culture and has even become part of local wisdom for centuries. The traditions of harmony, peace, mutual respect, tolerance and mutual cooperation have become the basis for patterns of religious moderation and have an important role in building religious harmony, as is the case in Banjar Tuka, Dalung Village. Patterns of religious moderation have been embedded in the construction of beliefs at personal and social levels, preserved through traditions and noble teachings, displayed in cultural works as markers of the presence of patterns of religious moderation in society. Starting from several cases of religious intolerance and social conflict based on religion, the Indonesian state needs to promote religious moderation. Because, with a moderate attitude in religion, harmony between religious communities can be achieved. The pattern of religious moderation needs to be implemented continuously and in a balanced manner to be able to establish community unity and unity towards a safe, peaceful, prosperous and harmonious society.